Policies affecting the supply and access of opioid analgesics: a scoping review protocol. Issue 5 (May 2020) - Chiu, Kellia; McDonald, Sally; Legg, Tess; Karanges, Emily A.; Bero, Lisa
ABSTRACT: Objective: This scoping review aims to describe and map the range of evaluated policies that affect the supply and access of opioids for analgesic therapy. Introduction: There has been increasing concern regarding the rise in opioid analgesic misuse and related harms, including overdose deaths. In response, policies have been developed and implemented to reduce the burden of opioid-related problems, including strategies that aim to affect the supply and/or access of opioid analgesics. However, little is known about the range and nature of these policies, including whether they have been evaluated for effectiveness and how. Inclusion criteria: Studies to be included must evaluate the effectiveness of policies directly designed to affect the supply and/or access of opioids for analgesic therapy, and measure clinical and health services outcomes quantitatively. Studies that assessed interventions or factors impacting the use of these policies, measured only utilization of the policy itself, and/or measured outcomes regarding attitudes and behaviors towards these policies will be excluded. Literature on policies for the treatment and management of opioid abuse, overdose, or addiction will be excluded. Methods: Multiple databases will be searched including MEDLINE, Embase, PsycINFO, Scopus, and Web of Science using keywords, indexed terms, and phrases for the following concepts: opioid, policy, evaluation, and clinical context. Each included study will be rated using a modified version of the JBI Levels of Evidence framework. Details on included policies and their assessment will be extracted, and results presented in diagrams and tables.